Harmonic Analysis of Three-phase Fixed Capacitor–thyristor Controlled Reactor under Balanced and Unbalanced Conditions - Jayababu Badugu; Y. P.Obulesu; Ch. Saibabu (IAES International Journal of Robotics and Automation (IJRA), 2018)
Three-phase Fixed Capacitor Thyristor Controlled Reactor is widely used for reactive power compensation in power systems because of reduced cost and high reliability.  The problem with FC-TCR is that to generate current harmonics when it is partially conducting. When this harmonic current is interacted with system impedance, voltage waveform will distorted. This harmonic pollution is undesirable in power systems. Therefore, it is important to know the harmonic behaviour of three-phase FC-TCR before they can be used in a power system network. This paper presents the harmonic analysis of three-phase FC-TCR operating under balanced and unbalanced conditions. This analysis is useful to design the harmonic filter to reduce the harmonic pollution in power systems.The proposed work is implemented in MATLAB environment.